2019
DOI: 10.1053/j.ajkd.2019.03.421
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis Markers and Recovery From Acute Kidney Injury: A Piece of the Puzzle?

Abstract: A cute kidney injury (AKI) occurs in 5% to 42% of patients undergoing cardiac surgery and represents a considerable burden in terms of health outcomes and hospital costs. 1 In this population, severe or prolonged AKI

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The recent Translational Research Investigating Biomarker Endpoints for AKI study found that high postoperative plasma levels of VEGF A isoform and placental growth factor were associated with reduced risk for AKI and mortality (14). The present finding of high levels of Wnt-7a could coincide with VEGF effects on angiogenesis and endothelial remodeling, thus biomarkers associated with vascular regeneration could be potential biomarkers of kidney recovery (42). c-Myc is a transcription factor that activates the expression of growth-related genes (43).…”
Section: Discussionmentioning
confidence: 73%
“…The recent Translational Research Investigating Biomarker Endpoints for AKI study found that high postoperative plasma levels of VEGF A isoform and placental growth factor were associated with reduced risk for AKI and mortality (14). The present finding of high levels of Wnt-7a could coincide with VEGF effects on angiogenesis and endothelial remodeling, thus biomarkers associated with vascular regeneration could be potential biomarkers of kidney recovery (42). c-Myc is a transcription factor that activates the expression of growth-related genes (43).…”
Section: Discussionmentioning
confidence: 73%
“…43 As a result, angiogenesis has since been proposed as a possible determinant of recovery from AKI and its long-term effects. 44 Ltbp4S -knockdown resulted in lower CD31 and CD105 expression on days 1 and 3 post-IRI surgery in the mouse model, whereas addition of LTBP4 resulted in increased angiogenesis in both HUVECs and human aortic endothelial cells. We previously reported a relationship between angiogenesis and LTBP4, as demonstrated by the increase in VEGFR1 and VEGFR2 expression in LTBP4-conditioned media-cultured HUVECs.…”
Section: Discussionmentioning
confidence: 84%